The contribution of Electronic Records Management towards Organisational Performance: A case study of Stanbic Bank-Kabale Branch. - Kembabazi, Betty (Kabale University, 2023)
The purpose of the study was to examine the contribution of electronic records management towards organizational performance at Stanbic Bank Kabale branch. The study's specific objectives were to establish the role of electronic records management on Stanbic Bank's performance, to identify the challenges to effective management of electronic records management on Stanbic Bank's performance, and to identify solutions to the challenges to effective management of electronic records management at Stanbic Bank. The researcher used a descriptive research design with qualitative and quantitative methods and sampled 100 respondents purposefully using the sample size determination table of Krejcie and Morgan. The questionnaires used by the researcher were both open-ended and closed-ended. The study findings revealed that improvement in efficiency and productivity was the major benefit of ERM; on the challenges facing the effective management of electronic records management, the study findings revealed that most of the respondents answered that access and security were the major challenges facing ERM; and on the solutions to the challenges facing the effective management of electronic records management, the study findings revealed that most respondents answered that human resource training was the best solution to the challenges facing the effective management of electronic records management at Stanbic Bank. Lastly, the researcher recommended the construction of ERMS facilities, improve ERMS security, encourage corroborations, have government support, and provide maximum training as better solutions for the topic under study.